Cyrkularność w definiowaniu przez postulaty pojęcia wiedzy logicznej - Vilanova Arias, Javier (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2005)
In this paper I critically evaluate the Implicit Definition Theory and its possibility of resolution of two main problems concerning logical knowledge: the explication and the justification. I point at five results that can be obtained: apriority, factuality, normativity applicability and non-circularity. I argue that in case of explication all mentioned results can be obtained but in case of justification the circularity is inevitable. In the last paragraph I propose a solution of this problem.